Hydrolysis-resistant nylon material and application thereof
Through the components and process treatment of specific proportions, nylon materials with excellent tensile strength, bending strength and hydrolysis resistance and alcoholylation resistance were prepared, which solved the problem that existing nylon materials are prone to degradation in humid environments and poor hydrolysis resistance at high temperatures. The problem of this achieves good performance maintenance and improved yellowing resistance at high temperatures.
Patent Information
- Application Number
- CN202411662303.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
Existing hydrolysis-resistant nylon materials are prone to degradation in humid environments, with poor performance, and poor hydrolysis resistance at high temperatures, resulting in poor yellowing resistance and mechanical properties.
Using specific proportions, including nylon, polyvinyl chloride, glass fiber, compatibilizer, hydrolyzer, light stabilizer, thermal stabilizer and lubricant, processed by high mixer and twin screw extruder nylon materials with excellent tensile strength, bending strength and hydrolysis resistance to alcoholylation were prepared.
It improves the service life and stability of nylon materials in humid environments, enhances the hydrolysis resistance and alcoholylation resistance at high temperatures, reduces the decrease in bending strength after hydrolysis and alcoholylation, and has good yellowing resistance.
Smart Images

Figure BDA0005143736410000041 
Figure BDA0005143736410000051 
Figure BDA0005143736410000052
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nylon materials, and in particular relates to a hydrolysis-resistant nylon material and an application thereof. Background Art
[0002] Nylon materials are widely used in clothing, automotive parts, and electronic packaging due to their excellent mechanical properties, wear resistance, and cost-effectiveness. However, the molecular structure of nylon makes it extremely sensitive to hydrolysis, especially in a humid environment, where it is prone to degradation, resulting in a decrease in material performance. Therefore, with the acceleration of industrialization and the enhancement of environmental awareness, the research on hydrolysis-resistant nylon materials has gradually become a hot topic in the field of polymer materials science.
[0003] Hydrolysis-resistant nylon material is a material compounded by adding hydrolysis-resistant agents and other substances to traditional nylon, aiming to enhance its ability to resist erosion by water molecules. This material enhances the interaction between nylon molecular chains by introducing specific chemical substances, thereby slowing down the rate of hydrolysis reaction. Compared with ordinary nylon, hydrolysis-resistant nylon improves its service life and stability in humid environments, which has led to an increasing demand for high-performance hydrolysis-resistant nylon in the market. However, there are still problems such as yellowing resistance and poor mechanical properties, and hydrolysis resistance at high temperatures is still poor. Therefore, based on the above problems, it is urgent to develop new hydrolysis-resistant nylon materials, which can not only meet market demand, but also help promote technological progress and sustainable development of related industries. Summary of the invention
[0004] The object of the present invention is to provide a hydrolysis-resistant nylon material and application thereof to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions: On the one hand, the present invention provides a hydrolysis-resistant nylon material, which comprises the following components in parts by weight: 35-70 parts of nylon, 15-30 parts of polyvinyl chloride, 30-50 parts of glass fiber, 2-10 parts of compatibilizer, 0.5-2 parts of anti-hydrolysis agent, 0.5-2 parts of light stabilizer, 1-3 parts of lubricant, 0.1-0.5 parts of silicone surfactant, and 0.5-3 parts of heat stabilizer;
[0006] The light stabilizer is a benzophenone light stabilizer and a triazine light stabilizer.
[0007] Furthermore, the heat stabilizer is prepared by reacting benzoic acid, maleic anhydride, triethylene glycol and metal salt.
[0008] Furthermore, the metal salt is zinc acetate.
[0009] Furthermore, the preparation method of the heat stabilizer comprises the following steps:
[0010] (1) adding benzoic acid, triethylene glycol, a catalyst and an organic solvent into a first reactor, and performing a reflux reaction at 180-210° C., and purifying the reaction after the reaction is completed to obtain a first intermediate;
[0011] (2) under a nitrogen atmosphere, adding maleic anhydride and the first intermediate obtained in step (1) into a second reactor, and then heating and stirring to a temperature of 80-100° C. to allow sufficient reaction to obtain a second intermediate;
[0012] (3) After placing the second intermediate of step (2) into a third reactor, setting the temperature of the third reactor to 80-100° C., slowly adding the metal salt, after the addition is completed, setting the temperature of the third reactor to 110-130° C., allowing sufficient reaction, and after the reaction is completed, performing reduced pressure distillation to obtain a thermal stabilizer.
[0013] Furthermore, the molar ratio of benzoic acid to triethylene glycol in step (1) is 0.8-1:1; the molar ratio of maleic anhydride in step (2) to the first intermediate obtained in step (1) is 1:(0.8-1.2).
[0014] Furthermore, the benzophenone-based light stabilizer is at least one of 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.
[0015] Furthermore, the benzophenone light stabilizer is 2-hydroxy-4-n-octyloxybenzophenone.
[0016] Furthermore, the triazine light stabilizer is 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, wherein the CAS number of 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (i.e., antioxidant 3114) is 27676-62-6.
[0017] Furthermore, the mass ratio of the benzophenone light stabilizer to the triazine light stabilizer is 1:1.5-3.
[0018] Furthermore, the anti-hydrolysis agent is polycarbodiimide.
[0019] Furthermore, the lubricant includes but is not limited to ethylene bisstearamide, and the CAS number of ethylene bisstearamide is 110-30-5.
[0020] Furthermore, the nylon is at least one of nylon 6 and nylon 66.
[0021] Furthermore, the compatibilizer is at least one of maleic anhydride grafted polypropylene, silane grafted polypropylene, glycidyl methacrylate grafted polypropylene, and methacrylic acid grafted polypropylene.
[0022] Furthermore, the compatibilizer is maleic anhydride grafted polypropylene.
[0023] On the other hand, the present invention also provides an application of a hydrolysis-resistant nylon material in preparing auxiliary parts of automobile engines.
[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the hydrolysis-resistant nylon material prepared by the present invention has excellent tensile strength and flexural strength, and has good hydrolysis and alcoholysis resistance. The flexural strength decreases less after hydrolysis and alcoholysis. Even if the temperature during the hydrolysis and alcoholysis resistance test continues to increase, the flexural strength after hydrolysis and alcoholysis does not change significantly. The hydrolysis and alcoholysis resistance at high temperature is good, and the material has good yellowing resistance. DETAILED DESCRIPTION
[0025] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0026] In the following embodiments, except for the heat stabilizer A, the other compound monomers and related reagents used can be purchased from the market, among which nylon 6 was purchased from Shanghai Qiling Plastic Technology Co., Ltd. with the item number PA6UBC13B01; nylon 66 was purchased from Shanghai Qiling Plastic Technology Co., Ltd. with the item number A3EG10A3EG301; polyvinyl chloride was purchased from Henan Dinghao Chemical Co., Ltd. with the model number SG-5; glass fiber was purchased from Hangzhou Gaoke Composite Materials Co., Ltd. with the model number EC; maleic anhydride grafted polypropylene was purchased from Guangzhou Zhongjie Chemical Technology Co., Ltd. with the item number zj001; polycarbodiimide was purchased from Guangzhou Hangeng New Materials Co., Ltd. with the model number HG-120; and silicone surfactant was purchased from Nantong Jiuze Chemical Co., Ltd.
[0027] The preparation method of heat stabilizer A comprises the following steps:
[0028] (1) adding 5.4 mol of benzoic acid, 6 mol of triethylene glycol, tetraisopropyl titanate and 200 mL of toluene into a first reactor, and performing reflux reaction at 180° C., washing with water, and removing toluene and water by vacuum distillation to obtain a first intermediate, wherein the amount of tetraisopropyl titanate added is 0.15% of the total mass of benzoic acid and triethylene glycol, and the first intermediate is a hydroxyl-containing ester compound;
[0029] (2) under a nitrogen atmosphere, adding 3 mol of maleic anhydride and 3 mol of the first intermediate obtained in step (1) into a second reactor, and then heating and stirring to a temperature of 90° C. to react fully to obtain a second intermediate, which is a carboxyl ester compound;
[0030] (3) After placing 2 mol of the second intermediate obtained in step (2) into a third reactor, the temperature of the third reactor was set to 90° C., and then 1 mol of zinc acetate was slowly added. The addition was completed within 1 hour, and then the temperature of the third reactor was set to 120° C. to allow sufficient reaction. After reacting for 2 hours, the reaction was performed under reduced pressure distillation to obtain a thermal stabilizer A.
[0031] The preparation method of the hydrolysis-resistant nylon material of Examples 1-5 and Comparative Examples 1-2 comprises the following steps:
[0032] (1) Place nylon, polyvinyl chloride, compatibilizer, and silicone surfactant in a high-speed mixer and stir until uniformly mixed, then add a hydrolysis resistance agent, a light stabilizer, a heat stabilizer, and a lubricant, and continue stirring until the raw materials are uniformly mixed. The stirring speed is 250 r / min;
[0033] (2) The raw materials mixed in step (1) are added into a twin-screw extruder through a first feeder of the twin-screw extruder, and glass fiber is added into the twin-screw extruder from a second feeder of the twin-screw extruder for extrusion granulation. The temperature of each zone of the twin-screw extruder is controlled at 260° C., 265° C., 275° C., 275° C., 280° C., 280° C., 270° C., and 260° C. The rotation speed of the main machine is 300 r / min, the feeding rate is 30 r / min, the temperature of the die head is 260° C., and the raw materials are melt-blended in the twin-screw extruder to obtain a hydrolysis-resistant nylon material.
[0034] The required components and the contents of each component in Examples 1-5 and Comparative Examples 1-2 are shown in Table 1-2:
[0035] Table 1
[0036]
[0037]
[0038] Table 2
[0039]
[0040]
[0041] The hydrolysis-resistant nylon materials obtained in Examples 1-5 and Comparative Examples 1-2 were tested for tensile strength, flexural strength, hydrolysis resistance and alcoholysis resistance. The test method is as follows, wherein the tensile strength and flexural strength test equipment is a Zwick Z010 electronic tensile testing machine:
[0042] Tensile strength: Test standard is ISO 527-2-2012, speed is 5mm / min, unit is MPa;
[0043] Bending strength: Test standard is ISO-178, span is 64mm, speed is 2mm / min, unit is MPa;
[0044] Hydrolysis and alcoholysis resistance test (120°C): Immerse the sample in a constant temperature oil bath containing ethylene glycol aqueous solution (the mass ratio of ethylene glycol to water is 1:1), raise the temperature of the constant temperature oil bath to 120°C, and keep it for 150 hours. Then test the bending strength of the sample after corrosion, in MPa.
[0045] Hydrolysis and alcoholysis resistance test (140°C): Immerse the sample in a constant temperature oil bath containing ethylene glycol aqueous solution (the mass ratio of ethylene glycol to water is 1:1), raise the temperature of the constant temperature oil bath to 140°C, and keep it for 150 hours. Then test the bending strength of the sample after corrosion, in MPa.
[0046] Yellowing resistance (170°C): The color difference value change (△E) of the test sample before and after baking at 170°C for 24 hours in an oven was tested. The test instrument was purchased from HunterLab UltraScan PRO colorimeter from Beijing Jinli Tongjian Environmental Technology Co., Ltd.
[0047] The test results are shown in Table 3-4, as follows:
[0048] Table 3
[0049]
[0050] Table 4
[0051]
[0052] By comparing Example 1 with Examples 4-5, it can be seen that the hydrolysis-resistant nylon material prepared by the heat stabilizer provided in the present application has better tensile strength, flexural strength and yellowing resistance, and the flexural strength decreases less after hydrolysis and alcoholysis at a temperature of 120°C, and the hydrolysis and alcoholysis resistance performance is good. After the temperature during the hydrolysis and alcoholysis resistance test is further increased (the increased temperature is 140°C), the flexural strength after hydrolysis and alcoholysis does not change significantly, and the hydrolysis and alcoholysis resistance performance at high temperature is good;
[0053] From the comparison between Example 1 and Comparative Example 1, it can be seen that the combination of benzophenone light stabilizer and triazine light stabilizer can improve the hydrolysis resistance and alcoholysis resistance of the hydrolysis-resistant nylon material at high temperature to a certain extent while maintaining good tensile strength and flexural strength, and significantly improve the yellowing resistance;
[0054] From the comparison between Example 1 and Comparative Example 2, it can be seen that the use of the heat stabilizer provided by the present application, and the use of the benzophenone light stabilizer and the triazine light stabilizer in combination, the prepared hydrolysis-resistant nylon material has excellent tensile strength and flexural strength, and the flexural strength decreases less after hydrolysis and alcoholysis at a temperature of 120°C, and the hydrolysis and alcoholysis resistance is good. Even if the temperature during the hydrolysis and alcoholysis resistance test is further increased (the increased temperature is 140°C), the flexural strength after hydrolysis and alcoholysis does not change significantly, the hydrolysis and alcoholysis resistance at high temperature is good, and the yellowing resistance is significantly improved;
[0055] In summary, the components and contents provided in the present application make the hydrolysis-resistant nylon material have excellent tensile strength and flexural strength, good hydrolysis and alcoholysis resistance, and the flexural strength decreases less after hydrolysis and alcoholysis. Even if the temperature during the hydrolysis and alcoholysis resistance test continues to increase, the flexural strength after hydrolysis and alcoholysis does not change significantly. The hydrolysis and alcoholysis resistance at high temperature is good, and it has good yellowing resistance.
[0056] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A hydrolysis-resistant nylon material, characterized in that: The hydrolysis-resistant nylon material comprises the following components in parts by weight: 35-70 parts of nylon, 15-30 parts of polyvinyl chloride, 30-50 parts of glass fiber, 2-10 parts of a compatibilizer, 0.5-2 parts of an anti-hydrolysis agent, 0.5-2 parts of a light stabilizer, 1-3 parts of a lubricant, 0.1-0.5 parts of an organic silicon surfactant, and 0.5-3 parts of a heat stabilizer; The light stabilizer is a benzophenone light stabilizer and a triazine light stabilizer.
2. The hydrolysis-resistant nylon material according to claim 1, characterized in that: The heat stabilizer is prepared by reacting benzoic acid, maleic anhydride, triethylene glycol and metal salt.
3. The hydrolysis-resistant nylon material according to claim 2, characterized in that: The preparation method of the thermal stabilizer comprises the following steps: (1) adding benzoic acid, triethylene glycol, a catalyst and an organic solvent into a first reactor, and performing a reflux reaction at 180-210° C., and purifying the reaction after the reaction is completed to obtain a first intermediate; (2) under a nitrogen atmosphere, adding maleic anhydride and the first intermediate obtained in step (1) into a second reactor, and then heating and stirring to a temperature of 80-100° C. to allow sufficient reaction to obtain a second intermediate; (3) After placing the second intermediate of step (2) into a third reactor, setting the temperature of the third reactor to 80-100° C., slowly adding the metal salt, after the addition is completed, setting the temperature of the third reactor to 110-130° C., allowing sufficient reaction, and after the reaction is completed, performing reduced pressure distillation to obtain a thermal stabilizer.
4. The hydrolysis-resistant nylon material according to claim 3, characterized in that: The molar ratio of benzoic acid to triethylene glycol in step (1) is 0.8-1:1; the molar ratio of maleic anhydride in step (2) to the first intermediate obtained in step (1) is 1:(0.8-1.2).
5. The hydrolysis-resistant nylon material according to claim 1, characterized in that: The benzophenone light stabilizer is at least one of 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.
6. The hydrolysis-resistant nylon material according to claim 1, characterized in that: The triazine light stabilizer is 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione.
7. The hydrolysis-resistant nylon material according to claim 6, characterized in that: The mass ratio of the benzophenone light stabilizer to the triazine light stabilizer is 1:1.5-3.
8. The hydrolysis-resistant nylon material according to claim 3, characterized in that: The compatibilizer is at least one of maleic anhydride grafted polypropylene, silane grafted polypropylene, glycidyl methacrylate grafted polypropylene, and methacrylic acid grafted polypropylene.
9. The hydrolysis-resistant nylon material according to claim 1, characterized in that: The nylon is at least one of nylon 6 and nylon 66.
10. Use of the hydrolysis-resistant nylon material according to any one of claims 1 to 9 in preparing auxiliary parts of automobile engines.
Citation Information
Cited By
Hydrolysis-resistant reinforced high-temperature nylon composite material and preparation method thereof
CN120248608A